Teacher-in-Role: Contributions to teaching children in Early Childhood Education (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article discusses the presence of theater specialists among Early Childhood Education teachers in Florianópolis, presenting Drama as a powerful approach to teaching and experiencing theatre to children at this stage of Basic Education. Through the teacher-in-role strategy, characters such as Sheila Enxerida and Fortroide provide a theatrical experience in which children and teachers become creative partners. Throughout the text, we argue that the presence of theatre teachers and theatrical language in NEIMs significantly expands children's expressive and bodily experiences.
Keywords: drama; teacher-in-role; early childhood Education; theatrical language; NEIM of the future